Job and the Pharisees - Gorringe, Timothy 1946- (1986)
The concern to learn and profit from the past experience of exile and restoration and to implement the command “Be holy as I am holy” underlies both the dialogue of Job and later Pharisaic theology; to reflect on one is to clarify the other.